How do you solve #-\frac { 3} { 7} + y = - \frac { 5} { 6}#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Pallu Share
Sep 21, 2017

Answer:

# y = -17 / 42 #

Explanation:

# -3/7 + y = -5/6 #

Keep the variable on left- hand- side and take the rest on right - hand - side of the equation. Apply rule of transposition.

# y = - 5/6 + 3/7#

Making the denominators same

# y =(- 5/6 ) # x # (7/7)+ 3/7# x # (6/6)#

#y = (- 35 + 18 ) /42 #

# y = -17 / 42 #

Was this helpful? Let the contributor know!
1500
Impact of this question
Answer impact map
16 views around the world
You can reuse this answer
Creative Commons License